Poster 196: Articular Chondrocytes in Hip Femoroacetabular Impingement Present a Less Catabolic Phenotype than Late Stage of Disease. Issue 7 (30th July 2022) - Kamenaga, Tomoyuki; Shen, Jie; Wu, May; Brophy, Robert; Clohisy, John; O'Keefe, Regis; Garrido, Cecilia Pascual
Objectives: Pathophysiologic mechanisms during osteoarthritis (OA) have been primarily identified using tissues harvested from end stage of disease. However, it is likely that the disease-initiating molecular changes have already occurred in early-stage diseased joints. Femoroacetabular impingement (FAI) has an etiologic role in up to 50% of hip osteoarthritis (OA) and offers a unique opportunity to study molecular changes during early stage OA. Cartilage samples from the impingement zone of FAI patients express catabolic inflammatory molecules. Previously, we have confirmed that DNA methyltransferase 3B (DNMT3B) regulates post-natal articular cartilage homeostasis and 4 aminobutyrate aminotransferase (ABAT) is a downstream target for DNMT3B and attenuates catabolic gene expression. The purpose of the present study is to examine the catabolic state of ACs during progression of disease in hip FAI, specifically, to investigate the catabolic phenotype and to assess the expression levels of DNMT3B and ABAT during early (FAI) and late stage disease (OA-FAI). Methods: Full-thickness cartilage samples were collected from the anterolateral head-neck junction (impingement zone) of 11 patients. 5 patients underwent hip preservation surgery for symptomatic cam FAI (early stage OA- FAI) and 6 patients underwent total hip replacement for advanced OA secondary to cam FAI (late stage FAI-OA). As a non-disease (ND) group, 4 healthy samples were procured from hip joint cadavers. A liberator was used to harvest full thickness tissue samples for cartilage explant cultures. The cartilage tissues were washed several times using antibiotics and incubated at 37 °C and 5% CO2 for 24h. Subsequently, the explants were cultured in unstimulated conditions (no-treatment), under anabolic (TGFβ) and catabolic stimulus (IL-1β) for 48h. After culture, sections were stained with safranin O and fast green for histological analysis and cartilage degeneration was graded based on the Mankin score. RNA was isolated from explants, gene expression was analyzed via qPCR for the following specific markers: GADPH (housekeeping gene), DNMT3B, ABAT, MMP-13, and Type X collagen ( COL10A1 ) (Figure-1). Comparisons among three groups were performed using one-way analysis of variance followed by the post hoc Bonferroni correction test. Results: Histological Mankin-scores are shown in Figure-2. Cartilage samples without treatment in ND group showed normal hyaline cartilage. However, reduction in safranin-O staining with significant increase of Mankin-score was observed under catabolic stimulus of IL-1β (Figure-2A). Contrary, in early FAI and late FAI-OA group, degenerative changes including superficial irregularities with some clefts, cell cloning, and reduced staining was observed in unstimulated conditions and became more pronounced when treated with IL-1β (Figure-2A and B). Degenerative changes were alleviated by anabolic stimulus with TGFβ1 (Figure-2B). qPCR revealed that compared to ND group, the expression levels of ABAT, MMP-13 and COL10A1 were increase in the early-FAI and late FAI-OA confirming a catabolic phenotype. Contrary, expression of DNMT3B gradually declined as the disease progressed showing significant differences between early-FAI and late FAI-OA (Figure-3B). Remarkably, although histological findings were similar between early and late stage FAI, catabolic molecule expression varied between early and late stage of disease suggesting a more catabolic phenotype state for late stage of disease. Conclusions: This current study provides initial data regarding the catabolic state of human ACs in early and late stage of hip FAI disease and characterized a catabolic phenotype of ACs from impingement zone in FAI. Importantly, although histological findings were similar between early and late stage FAI, catabolic molecule expression varied suggesting a less catabolic phenotype for early stage of disease. Most interestingly, the expression of DNMT3B gradually decrease as the disease progresses, and ABAT expression increase. Identification of these changes of methylation profiles during disease progression can distinguish pre- and early disease states from end diseased state and could provide a potential intervention to stop the OA progression in the near future. Future interventional therapies will confirm if ACs from early stage of disease can be rescued to a normal phenotype.